Airway management in children with cleft palate and/or micrognathia. Issue 1 (January 2020) - Schaëfer, Simone; Beale, Victoria; Doherty, Catherine; Bruce, Iain A.
Abstract: Cleft lip and/or palate is the commonest congenital craniofacial abnormality affecting approximately 1 in 700 newborns each year. It comprises of a heterogenous group of disorders affecting facial growth and cosmesis, that are associated with increased risk of airway obstruction, sleep disordered breathing (SDB), glue ear and chronic ear disease, feeding difficulties, and failure to thrive (FTT). Cleft palate (CP) can be accompanied by an abnormally undersized jaw, known as micrognathia; although micrognathia can also be found in isolation. The craniofacial abnormalities found in these children can lead to a reduction in airway size due to the tongue falling backwards. The risk of airway obstruction ranges from intermittent airway collapse during sleep (obstructive sleep apnoea, OSA) to potentially life-threatening airway compromise necessitating intubation or a tracheostomy. This paper sets out to describe the pathophysiology of airway compromise in these children, recognising clinical symptoms and appropriate referral strategy, as well as a broad range of management options.